Caribbean youth development : issues and policy directions ' - World Bank; World Bank. (Washington, D.C. : World Bank, 2003)
This study uses an ecological framework to consider negative behaviors and outcomes observed among Caribbean youths, and also identify ways to enhance positive influences.
Includes bibliographical references (p. 123-127).
osc 9/8/16
Loans
Keywords: Youth - economic conditions; Youth - government policy; Youth - health and hygiene; Youth - social conditions; Youth - services for; Carribean Area